Polarization phenomena in the process e⁺ + e⁻ ↔ N + Ň in presence of two-photon exchange - Gakh, G.I.; E., Tomasi-Gustafsson (Вопросы атомной науки и техники, 2007)
General properties of the differential cross section and of various polarization observables are derived for the e⁺ + e⁻ ↔ N + Ň reaction, in presence of two-photon exchange. Polarization effects are investigated for longitudi-nally polarized electron beam and polarized antinucleon and/or polarized nucleon in the final state.